Biofouling in reverse osmosis water reclamation and desalination - Stanislaus Raditya Suwarno (2014)
Fresh water is essential for basic daily activities. However, the world is now facing a water scarcity problem – depletion of fresh water sources (groundwater and surface water) due to unbalanced water demand and supply. Water desalination by reverse osmosis (RO) technology provides a solution to the water shortage problem. However, the success of RO technology is challenged by biofouling – a phenomena related to biological material development which forms a sticky layer on the membrane surface.